Respostas estratégicas ao ambiente institucional e a performance exportadora: o caso dos empreendedores do setor vitivinícola da campanha gaúcha - RS - Borges, Diego Echevengua (2014)
Making use of the theoretical framework of institutional theory, in particular, the concepts responses strategies, Isomorphism and institutional entrepreneurship as well as using the three dimensions of experf scale to analyze the export performance of the three wineries objects of study, this study aim to check which strategic responses three exporting wineries of the region Gaucha Campaign-RS front the pressures of the institutional environment to increase their export performances. Characterized as a qualitative research, as a source of primary data semistructured interviews with three wine entrepreneurs Campaign Region were performed. The interviews were guided by a script (protocol) preset. For data analysis, the technique of content analysis proposed by Bardin (1977), in comparison with the theoretical frameworks worked in the study was used. It can be seen that the wineries in the study not only conform the pressures of the institutional environment, but also use strategies that are characterized by resistance and manipulation (Oliver, 1991). For example, according to the surveyed companies due to the high tax their economies of scale deteriorate in the domestic market itself. Considering this, the wineries Dunamis and Miolo in a isomorphic way make use of the strategy and tactics to resist attack, seeking along with associations representing the wine industry transform this disadvantage to gain more sales and, as a result, improve their processes and products. Given this same pressure, it was identified that the winery Cordillera de Santana saw the external market as a safety valve against high taxes.